Use of double wire-guided technique and transpancreatic papillary septotomy in difficult ERCP: 4-year experience - Huang, Connie; Kung, Jonathan; Liu, Yong; Tse, Audrey; Datta, Anuj; Singh, Inder; Eysselein, Viktor E.; Reicher, Sofiya (Endoscopy International Open, 2016)
Background and aims: Post-ERCP complications increase with repeated attempts at cannulation. We evaluated several advanced biliary cannulation techniques applied when the standard approach fails.Methods: In total, 1873 consecutive patients underwent ERCP at our institution during the period 2010 – 2014. Guidewire-assisted (GA) cannulation with no contrast injection until deep biliary cannulation was considered the standard technique. Advanced techniques used were double wire-guided (DWG) cannulation, transpancreatic papillary septotomy (TPS), and needle-knife sphincterotomy (NKS). When GA cannulation failed, DWG cannulation was usually attempted first if the pancreatic duct (PD) wire was in place; if that failed, TPS or NKS was performed. Alternatively, TPS or NKS were performed alone. A prophylactic pancreatic stent was placed with repeated PD cannulation or PD contrast injection. During the last 2 years of review, indomethacin suppositories were given post-procedure to all patients who underwent advanced techniques.Results: The overall biliary cannulation success rate was 97 % (1823/1873). Advanced techniques were used in 12 % of ERCPs (230/1873), with 87 % (200/230) success rate. DWG was used alone or in combination with other techniques in 58 % (134/230) of advanced cases, with 68 % (91/134) success rate. Biliary cannulation was achieved in 96 % (91/95) of procedures when DWG was used alone, 76 % (26/34) with TPS alone, 80 % (37/46) for NKS alone, and 84 % (46/55) with multiple techniques. The overall rate of post-ERCP pancreatitis was 0.4 %, with all patients treated conservatively.Conclusion: In our experience at an urban tertiary care center, use of advanced techniques in difficult ERCP improved the overall success rate of biliary cannulation after standard technique failure without a significant increase in complication rate.